Identification of bradykinins in solitary wasp venoms - Konno, K.; Palma, Mario Sergio [UNESP]; Hitara, I. Y.; Juliano, M. A.; Juliano, L.; Yasuhara, T. (Elsevier B.V., 2002)
Bradykinins were identified in three solitary wasp venoms. Purification and characterization of the venom extract of the scoliid wasp Megacampsomeris prismatica led to the identification of bradykinin and threonine(6)-bradykinin as the major peptide components. The survey of a number of extracts from solitary wasp venom by MALDI-TOF MS revealed that the venoms of two other scoliid wasps, Campsomeriella annulata annulata and Carinoscolia melanosoma fascinata, also contained Thr(6)-BK as one of the major components. Thus, this study showed the presence of bradykinins in some of the solitary wasp venoms. Moreover, it indicated that these peptides play a major role in their paralyzing action for prey capture because these bradykinins have been shown to block the synaptic transmission of the nicotinic acetylcholine receptor in the insect central nervous system. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: bradykinin; solitary wasp; venom; MALDI-TOF MS